2006
DOI: 10.1645/ge-747r.1
|View full text |Cite
|
Sign up to set email alerts
|

Description and Morphometrical Variability of a New Species of Ligophorus and of Ligophorus Chabaudi (Monogenea: Dactylogyridae) on Mugil Cephalus (Teleostei) From the Mediterranean Basin

Abstract: A comparative morphological study of specimens of Ligophorus spp. from Mugil cephalus in western Mediterranean and the Black Sea localities has been carried out, indicating the presence of 2 distinct forms, i.e., Ligophorus chabaudi and Ligophorus cephali n. sp. A detailed description of the latter and an up-to-date redescription of L. chabaudi are provided. The existence of these 2 morphological species was additionally supported by principal component analysis based on 19 metric characters of 87 specimens ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 8 publications
1
38
1
3
Order By: Relevance
“…Based on the features mentioned above, L. uruguayense differs from the following Mediterranean species described by (1) Euzet and Suriano (1977): L. szidati, L. chabaudi, L. macrocolpus, L. acuminatus, L. minimus, L. heteronchus, L. angustus, L. imitans, L. confusus;(2) Euzet and Sanfilippo (1983): L. parvicirrus; (3) Sarabeev et al (2005): L. mediterraneus; and (4) Rubtsova et al (2006): L. cephali, on the basis of the shapes of the ventral bar and anchors, the accessory piece of the penis and the vaginal aperture, the host species and the geographic distribution. Additionally, Ligophorus uruguayense differs from L. euzeti Dmitrieva et Gerasev, 1996, L. gussevi, L. llewellyni Dmitrieva, Gerasev et Pron'kina, 2007, and the three recently described species from the Japan Sea by Rubtsova et al (2007): L. domnichi, L. cheleus and L. pacificus, mainly in the shape of the accessory piece of the penis, the host species and the geographic distribution.…”
Section: Ligophorus Uruguayense Sp Nov From Mugil Platanus In Urugumentioning
confidence: 91%
See 3 more Smart Citations
“…Based on the features mentioned above, L. uruguayense differs from the following Mediterranean species described by (1) Euzet and Suriano (1977): L. szidati, L. chabaudi, L. macrocolpus, L. acuminatus, L. minimus, L. heteronchus, L. angustus, L. imitans, L. confusus;(2) Euzet and Sanfilippo (1983): L. parvicirrus; (3) Sarabeev et al (2005): L. mediterraneus; and (4) Rubtsova et al (2006): L. cephali, on the basis of the shapes of the ventral bar and anchors, the accessory piece of the penis and the vaginal aperture, the host species and the geographic distribution. Additionally, Ligophorus uruguayense differs from L. euzeti Dmitrieva et Gerasev, 1996, L. gussevi, L. llewellyni Dmitrieva, Gerasev et Pron'kina, 2007, and the three recently described species from the Japan Sea by Rubtsova et al (2007): L. domnichi, L. cheleus and L. pacificus, mainly in the shape of the accessory piece of the penis, the host species and the geographic distribution.…”
Section: Ligophorus Uruguayense Sp Nov From Mugil Platanus In Urugumentioning
confidence: 91%
“…The distance between the membranous processes of the ventral bar is not a reliable measurement because it differed between mounted and live specimens or the membranous processes could not be seen clearly. In contrast to Rubtsova et al (2006), no difficulty was found in obtaining an accurate measurement of the whole length of the penis either for live or mounted specimens.…”
Section: Ligophorus Uruguayense Sp Nov (Figs 2-4)mentioning
confidence: 91%
See 2 more Smart Citations
“…Slides were then mounted in Kaiser's glycerol-gelatin and examined under a microscope at 100× magnification. The specimens were identified as L. cephali on the basis of morphological traits (haptoral and copulatory structures) based on Rubtsova et al (2006), Dmitrieva et al (2009 and Sarabeev et al (2013).…”
Section: Study Site Host and Parasite Collectionmentioning
confidence: 99%